2021
DOI: 10.1093/rheumatology/keab722.032
|View full text |Cite
|
Sign up to set email alerts
|

P040 Effect of parental smoking on Juvenile Idiopathic Arthritis activity

Abstract: Background Juvenile idiopathic arthritis (JIA) is an heterogeneous group of autoimmune diseases considered as the main cause of chronic arthritis among children and teenagers. This group of children is thought to be more vulnerable because of chronic inflammation and long-term immunosuppressive therapy. Passive smoking, which is a major health problem, is likely to be particularly harmful for these children whose immunity is already compromised by their disease. The aim of our study was to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Overall, exposure to secondhand smoking has a deep impact on child development. It is not only considered as a risk factor of developing JIA [ 51 , 52 ] but it essentially increases the probability of CVD developing in adolescents and young adults [ 53 ], including those suffering from autoimmune arthritides [ 54 ]. Evidence from Young Finns The Cardiovascular Risk revealed that having both parents smoke resulted in vascular age 3.3 years greater in young adulthood when compared to having neither parent smoke [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, exposure to secondhand smoking has a deep impact on child development. It is not only considered as a risk factor of developing JIA [ 51 , 52 ] but it essentially increases the probability of CVD developing in adolescents and young adults [ 53 ], including those suffering from autoimmune arthritides [ 54 ]. Evidence from Young Finns The Cardiovascular Risk revealed that having both parents smoke resulted in vascular age 3.3 years greater in young adulthood when compared to having neither parent smoke [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies has analyzed the prevalence of smoking among adolescents and adults with JIA; however, chronic diseases, defined as disability or illness lasting >6 months and requiring ongoing medical care, are a confirmed risk factor predisposing them to smoking in the teenage years and early adolescence [ 8 , 22 ]. In addition, exposure to tobacco smoke from fetal life to early childhood may be a risk factor for the development of JIA [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%